Analisis Kesalahan Siswa Berdasarkan Prosedur Newman Dalam Mengerjakan Soal Sistem Persamaan Linear Dua Variabel di SMP Negeri 1 Tondano - Thytania Walangare; Victor R. Sulangi; Anetha L. F. Tilaar (Departement of Mathematics Education, 2023)
This study aims to analyze students' errors in working on the System of Two Variable Linear Equations using the Newman procedure at SMP Negeri 1 Tondano. The research approach is a collective case study approach with a critical paradigm. Data was collected through interviews, written tests, observation, and documentation. In contrast, data analysis techniques include data reduction, presentation, and conclusion. The results obtained were (1) There was an error in the second stage of the Newman error procedure: students needed to understand all the questions the researcher gave. (2) In the Transformation section or the third stage in the Newman error procedure, students have not been able to convert the information obtained from the questions into a mathematical model (3) In the Process Skills section or the fourth stage, most students have not been able to work on the questions with good processing skills ( 4) then in the Answer Writing section there are primarily students who make mistakes when writing the final answer, where students do not write conclusions.